Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2008
DOI: 10.1145/1357054.1357067
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trajectories in shared interactive narratives

Abstract: Temporal trajectories can represent the complex mappings between story time and clock time that are to be found in shared interactive narratives such as computer games and interactive performances. There are three kinds. Canonical trajectories express an author's intended mapping of story time onto clock time as part of the plot and schedule of an experience. Participant trajectories reflect a participant's actual journey through story time and clock time as they interact with the experience. Historic trajecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 16 publications
1
51
0
2
Order By: Relevance
“…We begin by introducing the three source publications [27,29,28] that, according to the originators of trajectories, constitute the authoritative source of the framework. We introduce the main concepts and vocabulary of the framework so that we can refer to it in later discussions.…”
Section: The Source Trajectory Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…We begin by introducing the three source publications [27,29,28] that, according to the originators of trajectories, constitute the authoritative source of the framework. We introduce the main concepts and vocabulary of the framework so that we can refer to it in later discussions.…”
Section: The Source Trajectory Literaturementioning
confidence: 99%
“…The temporal trajectories framework [27] is based on the description of temporal structures in Day of the Figurines, a mixed-reality game by artist collective Blast Theory [10]. Temporal trajectories are defined the expression of a mapping between story time (as the game involves events unfolding over 24 hours in a fictional world) and clock time (the actual time in which the story is accessed).…”
Section: Temporal Trajectories In Shared Interactive Narrativesmentioning
confidence: 99%
“…For example, a slide has a fairly clear trajectory [32] in which a participant starts at the top and slides down, unless it is re-appropriated by children who wish to climb back up. Such a trajectory is likely to maintain a high throughput, as the duration of each experience is limited by the length of the slide.…”
Section: Different Designs Of Rides Offer Very Different Throughputsmentioning
confidence: 99%
“…To analyse the player's patterns of interaction the above study used 'Temporal Trajectories' [2] which maps the fictional 'story time' of the game against the real 'clock time' of the players, which was adopted within our study The Savvy group was motivated by being the first to solve the puzzles through effective collaboration yet the Random group was de-motivated when they found that all the puzzles had been solved and they could access all the answers. The respective temporal trajectories for the two groups are shown in Figure 3.…”
Section: Temporal Trajectoriesmentioning
confidence: 99%